MEMBANGUN KEUNGGULAN KOMPETITIF MELALUI PENCIPTAAN PENGETAHUAN - Elvy Maria (Bina Ekonomi, 2003)
We are in our very way in entering the New Era mostly associated with knowledge. Knowledge has become a huge and most frequently spoken theme in businessphere. It is believed among business academic communities and practitioners that knowledge will be the very central issue on competitive advantage. And, building competitive position or advantages means now to create new knowledge in advance of the competitors. However, it is not that all to be competitive are, then, to be very fast in transforming knowledge into innovations (product, process technology, and management) and to abandon them at the proper time; that is, when changes prevail. The roles of management required are as to create and to nurture a relevant and an encouraging habitat and atmosphere for learning. Indeed, it is human entity which does the learning. Therefore, to build competitive advantage is to encourage people to learn new knowledge, to create new knowledge upon old ones, and to innovate product, or technology, or management, upon new knowledge created.